EFFECTS OF GROUP COUNSELLING ON KNOWLEDGE, ATTITUDE AND PREFERENCE FOR DELIVERY METHOD IN WOMEN REFERRED TO COMPREHENSIVE HEALTH CENTRES OF HAMADAN FOR PRE-PREGNANCY CARE - Ghafari Azandariani, Maryam; Masoumi, Seyedeh Zahra; Kazemi, Farideh; Khodakarami, Batul (Journal of Postgraduate Medical Institute, 2021)
Objective: To investigate the effects of group counseling on knowledge, attitude and preference for birth method in women who received pre-pregnancy care. Methodology: This randomized clinical trial (IRCT20120215009014N239) study with two-group was conducted at Hamadan Comprehensive Health Centers from November 1, 2018 to March 20, 2019. A total of 240 women with pre-pregnancy records were randomly selected and then 90 eligible women were analyzed after being classified into intervention and control groups using the sequential allocation. The intervention group participated in four group counseling sessions. Data collection tool was a questionnaire containing demographic information, knowledge, attitude and preference for birth method. Data was analyzed using SPSS 20; descriptive and analytical tests were applied, where needed. Results: The mean age in two groups (Intervention & Control) was (26.73±4.02, 27.20±4.36) years respectively. Mean scores of knowledge and attitude (23.61±7.44 vs 23.78±6.17 & 67.68±12.68 vs 70.62±11.92 respectively) with preference for birth method had no significant difference between the two groups before the intervention, but the mean score of knowledge, and attitude was significantly higher in the intervention group after the intervention than the control group (43.88±4.85 vs 22.09±4.79 & 85.06±7.49 vs 66.87±7.41 respectively) (p <0.001). In delivery type preference, vaginal delivery preference was remarkably increased from 61.4% to 95.5% with p-value <0.001. Conclusion: Group counseling affected the women’s knowledge, positive attitude towards vaginal delivery and helping them to have informed preferences for birth method.